SKUTKI EMIGRACJI ZAROBKOWEJ RODZICÓW W ASPEKCIE ZAGROŻENIA DOBRA DZIECKA NA PODSTAWIE BADAŃ ANKIETOWYCH NAUCZYCIELI - Stojanowska, Wanda; Kosek, Mirosław (Zeszyty Prawnicze, 2017)
The Consequences of Parents Economical Emigration in the Context of a Threat to the Child’s Good on the Basis of the Teachers’ Surveys Research Summary The subject of the analysis is the results of the survey carried out in 2008 concerning teachers from 5 schools in Płock numbered 86. 62 of those teachers have had contacts with children, whose parents are economical emigrants. This group of respondents has provided most information amongst others such as who takes direct care of the child and what the symptoms of the parents’ and child’s separation negative consequences are. It has also turned out that a cooperation between teachers and family courts almost does not exist. The teachers are not familiar with article 572 of the Civil Procedure Code which provides for an obligation to notify about the instances of the abuse of the child’s good. or even if they know it, they do not apply it. It seems that teachers do not know that rule or feel reluctant to obey it. The research illustrates that teachers show enthusiasm and sensitivity. They help the so-called ‘Euro-orphans’ as much as they can. Their kind approach allows optimism.Nevertheless, it is necessary to establish a close cooperation between the school and the family court in order to use their full potentials. It would be useful if both the Education and Justice Departments could reach an agreement in order to improve the procedure of regulating the legal situation of the so-called Euro-orphans’ regarding parental authority and establishment of the legal guardianship.